2022
DOI: 10.3390/ijms231911629
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Heterogeneity of Brain Tumor Cells of Proneural and Mesenchymal Origin

Abstract: Brain-tumor-initiating cells (BTICs) of proneural and mesenchymal origin contribute to the highly malignant phenotype of glioblastoma (GB) and resistance to current therapies. BTICs of different subtypes were challenged with oxidative phosphorylation (OXPHOS) inhibition with metformin to assess the differential effects of metabolic intervention on key resistance features. Whereas mesenchymal BTICs varied according to their invasiveness, they were in general more glycolytic and less responsive to metformin. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…In a previous study [ 7 ], we described the metabolic preferences of proneural and mesenchymal BTICs and their response to the metabolic drug metformin. For that purpose, we performed glucose flux analyses, which demonstrated that mesenchymal BTICs are more glycolytic while proneural BTICs metabolize glucose more towards the pentose phosphate pathway.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous study [ 7 ], we described the metabolic preferences of proneural and mesenchymal BTICs and their response to the metabolic drug metformin. For that purpose, we performed glucose flux analyses, which demonstrated that mesenchymal BTICs are more glycolytic while proneural BTICs metabolize glucose more towards the pentose phosphate pathway.…”
Section: Resultsmentioning
confidence: 99%
“…One of the pathophysiological features of GB is aberrant tumor metabolism [ 5 ]. Whereas glucose metabolism has been extensively explored [ 6 , 7 ], there is still limited data on amino acid metabolism. In our previous work, we were able to demonstrate the metabolic preferences of distinct metabolic subtypes of glioma.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations